(3efgGL GdHjGf hOSJhQ GdCYjGf aj JQcjH GdCOhjI GdfGaYI ddEfSGfs - (3Gdchgjf GdYWGQ GdGSQGFjdj , OGhO Hf CHj fUQ Hf MaGX, CHh Gdefj,J (B608 (3g` s
(3ChdgG (B:s
(3CeGHYO (B: (3aEfi QeJ eLehYkG jchf LGeYkG dLejY CZQGV ade CLO cJGHkG deGQeJg , hdG CbQGHGPjf dCMO ef GdeJbOejf Ch GdeJCNQjf cGajkG ajeG bUOJg s
(3BNQgG (B:s
(3SYhW jbWY GdQYGa CjVkG (B((3ef Gdedci(B) (3bQWGS eMQb ,NeSI s
(3GfXQgG eY GdCbQGHGRjf ddSeQbfOj Qbe(B" 333"s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B143s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdKGfi (B- (3U (B262 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B327 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs